(untitled) (IIUC Studies, 2009)
The Management History Division (MHD) of the Academy of Management, NY records critical and scholarly discussion, refection and research in the arena of management history. It supports the development of historically informed analyses and explorations of management practices and of management philosophy and thought. The authors aim at focusing on three key members of MHD i.e. Charles Deck Wrege, James C. Worthy, and Alfred A Bolton who have contributed a lot in the field of management history during 1990s. Each of them has significant contribution to the area of management history and each has proved himself a teacher and intellectual leader in matters of fundamental concern to management history. Keywords: Academy of Management, Management History Division, Management Historian, Charles Deck Wrege, James C. Worthy, and Alfred A. Bolton. doi: 10.3329/iiucs.v3i0.2666 IIUC STUDIES Vol. - 3, December 2006 (p 73-82)